The artistic process of drawing in the city of Parintins-AM: from analog to digital - Reis, Giselle da Costa (Revista do Colóquio, 2024)
This study is the result of an undergraduate research that investigated the relationship between traditional and digital drawing in the artistic production of the city of Parintins, located in the state of Amazonas. Using a qualitative approach, the research involved interviews and questionnaires with artists working in both universes of drawing. Based on authors such as Sílvia Simões (2001), Pedro Costa (2021) and Débora Gasparetto (2013; 2016), the research shows how digital drawing is gradually redefining artistic production and preserving elements of local culture.